Design and Construction Fish Cool Box Using Combined Aluminum and Ethylene Vinyl Acetate (EVA) Materials - Fauzi Syah Putra; Fatoni, Khoerul; Aprilia Syah Putri; Citra, Lalik Salistia; Tirtana, Denta (International Journal of Marine Engineering Innovation and Research, 2026)
Abstract¾ Indonesia is one of the world’s leading producers and exporters of fresh and frozen fish; however, the economic value of its fishery exports remains relatively low due to quality deterioration caused by inadequate post-harvest handling, particularly during onboard storage. Small-scale fishers predominantly use conventional storage media such as styrofoam or fiber-based cool boxes with block ice, which often provide insufficient insulation and poor temperature stability. This study aimed to evaluate the thermal performance and ice utilization efficiency of an innovative laminated cool box constructed using a combination of aluminum plate, aluminum foil, ethylene-vinyl acetate (EVA) sponge, and fiberglass, compared with a conventional fiber-based cool box. An experimental design with two treatments and three replications was applied over a four-month period at the Capture Fisheries Laboratory, Politeknik Negeri Lampung. Cooling performance was assessed through optimal cooling tests, 24-h and 48-h temperature performance evaluations, ice efficiency analysis, and statistical comparison using an independent samples t-test. The results showed that the innovative cool box achieved a lower minimum temperature (−3 °C) and a faster cooling rate (0.50 °C min⁻¹) than the standard cool box (−1 °C; 0.29 °C min⁻¹). During the 48-h test, the innovative cool box maintained temperatures below 4.4 °C for up to 18 h, significantly longer than the standard cool box. Although the ice utilization efficiency of the innovative cool box (26.16%) was lower than that of the standard cool box (30.80%), its overall cooling performance and thermal stability were superior. These findings demonstrate the potential of the innovative cool box to improve fish quality preservation and support higher economic value in fisheries post-harvest handling.